Epicardial Fat Thickness as Cardiovascular Risk Factor and Therapeutic Target in Patients with Rheumatoid Arthritis Treated with Biological and Nonbiological Therapies. (10th December 2014) - Lima-Martínez, Marcos M.; Campo, Ediris; Salazar, Johanmary; Paoli, Mariela; Maldonado, Irama; Acosta, Carlota; Rodney, Marianela; Contreras, Miguel; Cabrera-Rego, Julio O.; Iacobellis, Gianluca
Abstract : Rheumatoid arthritis (RA) is a chronic inflammatory disease associated with high cardiovascular morbidity and mortality. Epicardial adipose tissue (EAT) thickness may act as a therapeutic target during treatments with drugs modulating the adipose tissue. We evaluate EAT thickness in RA patients treated with biological and nonbiological disease-modifying antirheumatic drugs (DMARDs). A cross-sectional study was conducted with a cohort of 34 female RA patients and 16 controls matched for age and body mass index (BMI). Plasma glucose, basal insulin, plasma lipids, and high-sensitivity C-reactive protein (hs-CRP) were assessed. EAT thickness and left ventricular mass (LVM) were measured by echocardiography. No significant differences in waist circumference (WC), blood pressure, fasting blood glucose, basal insulin, and lipid parameters were found between the groups. The control group showed lower concentrations (P = 0.033 ) of hs-CRP and LVM (P = 0.0001 ) than those of the two RA groups. Patients treated with TNF- α inhibitors showed significantly lower EAT thickness than those treated with nonbiological DMARDs (8.56 ± 1.90 mm versus 9.71 ± 1.45 mm;P = 0.04 ). Women with no RA revealed reduced EAT thickness (5.39 ± 1.52 mm) as compared to all RA patients (P = 0.001 ). Results suggest that RA patients have greater EAT thickness than controls regardless of BMI and WC.